SPE Annual Technical Conference and Exhibition 2006
DOI: 10.2118/102590-ms
|View full text |Cite
|
Sign up to set email alerts
|

Acid Fracturing or Proppant Fracturing in Carbonate Formation? A Rock Mechanic's View

Abstract: Acid fracturing is performed to improve well productivity in acid-soluble formations such as limestone, dolomite, and chalk. Hydrochloric acid is generally used to create an etched fracture, which is the main mechanism for maintaining the fracture open during the life of a well. Proppant fracturing is an alternative option that has been applied in carbonate formations. In certain areas, proppant fracturing has been used as a standard stimulation method for carbonate formations. There is no quantitative method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…As was mentioned previously, the efficiency of acid fracturing stimulations strongly depends on the ability of fracture to retain conductivity under closure stress. The mechanism of fracture closure is controlled by elastic deformation, compressive failure of contact points (asperities crushing), and viscous flow, also known as creeping effect (Abass et al 2006). The elastic deformation happens as a result of increasing effective minimum horizontal stress due to the reservoir depletion.…”
Section: Parameters Affecting Acid Fracture Conductivitymentioning
confidence: 99%
“…As was mentioned previously, the efficiency of acid fracturing stimulations strongly depends on the ability of fracture to retain conductivity under closure stress. The mechanism of fracture closure is controlled by elastic deformation, compressive failure of contact points (asperities crushing), and viscous flow, also known as creeping effect (Abass et al 2006). The elastic deformation happens as a result of increasing effective minimum horizontal stress due to the reservoir depletion.…”
Section: Parameters Affecting Acid Fracture Conductivitymentioning
confidence: 99%
“…A propped fracture is an alternative stimulation technique wherein acid is replaced with proppant slurry. Abbas et al and Suleimenova et al showed that a propped fracture is better at sustaining conductivity at higher closure stresses. Nevertheless, acid fracturing is a cheaper option that does not suffer from screenout complications.…”
Section: Introductionmentioning
confidence: 99%
“…18 The extraction of hydrocarbons results in increased stresses on the fracture surface, which, combined with the elevated temperatures, causes gradual plastic deformation of the reservoir rock (rock creeping). 19,20 Creeping, in turn, leads to reduction of the fracture width (conductivity reduction), presented in terms of a failure of asperities and embedment (indentation) of proppant into formation rock. 21−23 Researches have shown that the mechanical characteristics of the reservoir rock (hardness, Young's modulus), fracture surface roughness, proppant properties (type, size, concentration), and acid properties (type, reaction time) are critical factors that affect the decline of the fracture conductivity.…”
Section: Introductionmentioning
confidence: 99%